1987
DOI: 10.1007/bf00019796
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of various crack tip displacement based elastic-plastic fracture parameters to characterise ductile crack growth resistance

Abstract: There is continuing interest in defining a fracture parameter which is capable of characterising the ductile crack growth resistance o~" a material under conditions of large scale plasticity. The aim of this study is to assess the capability of a numberof, elastic-plastic fracture parameters for the case of a C-Mn steel. The fracture parameters considered are: the crack opening displacement at the original crack tip (CTOD); the crack opening angle at the growing crack tip (CTOA); and the crack opening displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…For ST37, direct CTODi measurements in [9] show that within certain ranges of geometry variations the CTODi value is quite constant. In [10] it was shown that for deeply notched bend type specimens the crack opening displacement at the growing crack tip (which is equivalent to CTOAc) measured in the central region of the specimen is unaffected by the specimen geometry. The material tested in [10] was a normalized C-Mn steel (BS 4360 43A) which has similar mechanical properties as ST37.…”
Section: Numerical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For ST37, direct CTODi measurements in [9] show that within certain ranges of geometry variations the CTODi value is quite constant. In [10] it was shown that for deeply notched bend type specimens the crack opening displacement at the growing crack tip (which is equivalent to CTOAc) measured in the central region of the specimen is unaffected by the specimen geometry. The material tested in [10] was a normalized C-Mn steel (BS 4360 43A) which has similar mechanical properties as ST37.…”
Section: Numerical Analysesmentioning
confidence: 99%
“…In [10] it was shown that for deeply notched bend type specimens the crack opening displacement at the growing crack tip (which is equivalent to CTOAc) measured in the central region of the specimen is unaffected by the specimen geometry. The material tested in [10] was a normalized C-Mn steel (BS 4360 43A) which has similar mechanical properties as ST37. In fact, the influence of the geometry variations on the local quantities such as CTODi and CTOAc, if any, may be quite different from that on the global load-displacement response of the specimens.…”
Section: Numerical Analysesmentioning
confidence: 99%
“…A similar formula to calculate the J-integral of a plain sided specimen was proposed in [ 14] and [ 15] where the J-integral of the total specimen was divided into a contribution of flat fracture in the center region of the specimen and a contribution of shear fracture near the side surface. In place of Bs, two times of the shear lip width were used.…”
Section: Aae and Aasmentioning
confidence: 99%
“…According to our model, the increment of the J-integral dJ due to an increment of the load-line displacement dVLL Can be calculated from the increments dJs and dJe of J in the plane stress part and plane strain part of the specimen with (5) dJ = ~dJ~ + (1 -~s)dJ~. (13) Similarly, due to (4) the increment of the crack extension da due to dVLL is da =/3~das + (1 -~)dae, (14) where da~ and da~ are crack extension increments of the plane stress part and the plane strain part, respectively. All d J, dJs, dJ~, da, das and dae are measured at the same load-line displacement.…”
Section: The Dependence Of the Crack Growth Resistance On The Specimementioning
confidence: 99%
See 1 more Smart Citation